Endogenous testosterone is associated with increased striatal response to audience effects during prosocial choices. (December 2020) - Li, Yansong; Météreau, Elise; Obeso, Ignacio; Butera, Luigi; Villeval, Marie Claire; Dreher, Jean-Claude
Highlights: Social status behavior is modulated by the fact to be observed by others (audience effect). The audience effect modulates prosocial behavior and striatal activity. Higher testosterone levels are correlated with greater striatal activity induced by the audience effect. Testosterone plays a key role in maintaining social status via modulation of the audience effect. Abstract: The role of testosterone on cognitive functions in humans remains controversial. One recent hypothesis suggests that this steroid hormone advances social status. As being observed by others is known to modulate a range of behaviors because of image concerns, we hypothesized that such an audience effect might be an important component of status seeking that is under the control of testosterone. Thus, we investigated to which extent testosterone levels are associated with the effect of being observed during prosocial choices and the neural mechanisms underlying this effect. We enrolled twenty-four male participants, aged 22.47 ± 2.62 years, in an fMRI experiment to examine the relationship between testosterone levels and brain activity engaged in deciding whether to accept or reject monetary transfers to two types of organizations (a positively evaluated organization and a negatively evaluated organization) in presence or absence of an audience. When comparing the public to the private condition, the rate of acceptance increased for the positively evaluated organization, while the rate of rejection increased for the negatively evaluated one. Higher testosterone levels were linked to greater activation in the striatum in the public compared to the private condition, regardless of the organization type. These results indicate a relationship between testosterone levels and striatal activity induced by the audience effect. These findings provide new insights on the role of testosterone in human social behavior.